A Review of Examining the Financial Performance of Makassar City through the Regional Financial and Asset Management Agency - Zainuddin Rahman; Syamsu Nujum; Hukma Ratu Purnama (PT Mattawang Mediatama Solution, 2023)
This research delves into evaluating the Financial Performance of the Regional Budget (APBD) within the context of the Regional Financial and Asset Management Agency in Makassar City from 2019 to 2021. The study uses primary and secondary data sources using a quantitative descriptive approach. Primary data is garnered through meticulous on-site observations and comprehensive documentation, while secondary data is meticulously curated from diverse sources. The study's revelations bring to light an intriguing facet: the financial performance of Makassar City's local budget, assessed via the regional financial effectiveness ratio, registers below the 100 percent mark, thus underscoring a realm of suboptimal efficiency. A particularly compelling narrative unfolds in the Growth Ratio of the city's Local Own Source Revenue (PAD) from 2019 to 2021, with a notable ascent to 5.9433 percent. This substantial growth rate represents a remarkable stride forward when juxtaposed with the antecedent growth ratio, which had lingered at a mere 2.022 percent. Drilling down into the specifics, the Growth Ratio of Local Source Revenue (PAD) analysis delineates a modest 0.4 percent figure for 2019, catapulting to an impressive 6.08 percent in the pivotal year of 2021. Further enhancing the tapestry of insights, the breakdown of the Growth Ratio of Local Revenue Expenditure (PAD) paints a vivid picture: it stood at 9.94 percent in 2019, reflecting a substantial surge, and maintained a commendable trajectory at 7.89 percent in the subsequent year of 2021.